Assessing the impact of a health education outreach project on cervical cancer awareness among Vietnamese-American women in San Diego - Eduardo Fricovsky; Mudassar Iqbal Arain; Binh Tran; Phuong Thao Nguyen; Tuyet Phan; Natalie Chang (AIMS Press, 2022)
The objective of this study was to assess the rate of effectiveness of cervical cancer awareness outreach among Vietnamese women in San Diego, USA. In collaboration with different community partners, educational seminars were hosted by student pharmacists in the Vietnamese community. We hypothesized that the seminars would increase cervical cancer awareness and encourage a positive outlook on obtaining annual Pap smears and HPV vaccines. The study design included pre- and post-intervention assessment surveys in either Vietnamese or English language. The surveys were administered to Vietnamese women who participated in the seminars. Eight seminars were hosted at local health fairs in San Diego. A total of 120 Vietnamese women participated in the seminars. Our study showed that educational seminars significantly improved the knowledge about cervical cancer, Pap smears and HPV vaccines. By comparing the pre- and post-intervention surveys, we observed an improvement in knowledge about cervical cancer (61% vs 93%, p < 0.001) and a positive change in the attitude towards obtaining a Pap smear within a year following the educational intervention (57% vs. 78%, p < 0.002). Therefore, we concluded that the educational health outreach seminars presented by student pharmacists are an effective educational model to help improve knowledge about cervical cancer and prevention among Vietnamese women.